2016
DOI: 10.1038/srep39191
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the regenerative and mineralogenic performances of the zebrafish caudal fin

Abstract: The ability of zebrafish to fully regenerate its caudal fin has been explored to better understand the mechanisms underlying de novo bone formation and to develop screening methods towards the discovery of compounds with therapeutic potential. Quantifying caudal fin regeneration largely depends on successfully measuring new tissue formation through methods that require optimization and standardization. Here, we present an improved methodology to characterize and analyse overall caudal fin and bone regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 60 publications
2
48
0
Order By: Relevance
“…using a panel of hundreds of compounds or small molecule libraries), the optimized operculum system described here, may provide a throughput higher than existing methodologies currently available to assess osteogenic compounds/activities. An approach using alizarin red S staining combined with morphometric analysis has already been demonstrated as an easy and accurate way to detect and quantify bone mineral deposition under fluorescence conditions (Bensimon-Brito et al, 2016;Cardeira et al, 2016). Other techniquese.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…using a panel of hundreds of compounds or small molecule libraries), the optimized operculum system described here, may provide a throughput higher than existing methodologies currently available to assess osteogenic compounds/activities. An approach using alizarin red S staining combined with morphometric analysis has already been demonstrated as an easy and accurate way to detect and quantify bone mineral deposition under fluorescence conditions (Bensimon-Brito et al, 2016;Cardeira et al, 2016). Other techniquese.g.…”
Section: Discussionmentioning
confidence: 99%
“…Other features, such as robustness, high fecundity and short generation time have reinforced the suitability of zebrafish as a laboratory animal. Various in vivo tools exist to study how drugs affect the skeleton (osteogenic or anti-osteogenic activities) (Laizé et al, 2014;Cardeira et al, 2016), including zebrafish mutant lines mimicking human skeletal disorders (Barrett et al, 2006;de Vrieze et al, 2014) and transgenic lines able to express fluorescent markers at sites of bone-related gene expression (Knopf et al, 2011a). These are valuable, both for the discovery of therapeutic molecules capable of rescuing skeletal pathologies and in studying their mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of exogenous administration of RA is however controversial. It has been shown to either impair fin regeneration by blocking blastema formation [44,52,53] or to enhance RA signaling and positively influence fin regeneration [51]. RA is not only a potent and effective inducer of embryonic stem cell differentiation [54] but also of zebrafish blastema cell differentiation (this study).…”
Section: Resultsmentioning
confidence: 83%
“…Osteoblasts may themselves exert a piloting function for other cell types, as the breakdown of ray-interray boundaries also affects other cell types, like fibroblasts and blood vessels [176]. An excess of RA results in a similar phenotype and induces an over-mineralized phenotype, by promoting bone matrix synthesis in osteoblasts [177]. Suppression of RA signaling by removing RA locally, as observed in the stump and in the proximal blastema, is a mechanism repeatedly utilized to guide osteoblast behavior towards the correct regenerative morphogenetic processes.…”
Section: Local Degradation Of Ra Controls Morphogenetic Processes Of mentioning
confidence: 99%
“…Reporter gene analyses showed that the fate of mature joint-forming osteoblast is not fixed, instead they differentiate to (regular) osteoblasts under RA, presumably by lifting an arrest in osteoblast differentiation or by transdifferentiation. If this effect contributes significantly to the over-ossification observed in RA-treated regenerates [176,177] has not been established yet. The findings underscore once more the requirement for precise spatio-temporal control of RA signaling during fin growth and regeneration.…”
Section: Ra Controls Cell Fate In the Preosteoblast Lineagementioning
confidence: 99%